2013
DOI: 10.1128/aem.01209-13
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Biofilm Formation in the Betaproteobacterium Burkholderia unamae CK43B Exposed to Exogenous Indole and Gallic Acid

Abstract: bBurkholderia unamae CK43B, a member of the Betaproteobacteria that was isolated from the rhizosphere of a Shorea balangeran sapling in a tropical peat swamp forest, produces neither indole nor extracellular polymeric substances associated with biofilm formation. When cultured in a modified Winogradsky's medium supplemented with up to 1.7 mM indole, B. unamae CK43B maintains its planktonic state by cell swelling and effectively degrades exogenous indole. However, in medium supplemented with 1.7 mM exogenous in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 45 publications
0
15
0
1
Order By: Relevance
“…Because indole modulates the biofilm formation of various bacteria (Lee et al ., 2007a; 2009; Kim et al ., ), we examined the effects of indole and indole‐3‐acetic acid on A . tumefaciens biofilm formation in 96‐well polystyrene plates.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because indole modulates the biofilm formation of various bacteria (Lee et al ., 2007a; 2009; Kim et al ., ), we examined the effects of indole and indole‐3‐acetic acid on A . tumefaciens biofilm formation in 96‐well polystyrene plates.…”
Section: Resultsmentioning
confidence: 99%
“…Because indole modulates the biofilm formation of various bacteria (Lee et al, 2007a;Kim et al, 2013), we examined the effects of indole and indole-3-acetic acid on A. tumefaciens biofilm formation in 96-well polystyrene plates. Indole at (0-1.0 mM) concentration dependently increased A. tumefaciens biofilm formation by up to 6.4 ± 1.6-fold ( Fig.…”
Section: Indole-enhanced a Tumefaciens Biofilm Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, indole inhibits the attachment of the fungal pathogen Candida albicans to intestinal epithelial HT-29 cells [56] and reduces the production of the virulence factor staphyloxanthin in Staphylococcus aureus [57]; both of these studies demonstrated virulence reduction in a Caenorhabditis elegans model [56,57]. Indole also inhibits cyanobacterial blooms caused by the formation of periphyton biofilms [58], induces biofilm formation by rhizospheric Burkholderia unamae [59], and delays predation by Bdellovibrio bacteriovorus [60]. It would be interesting to determine whether indole affects the virulence of other pathogens as well as those of environmental bacteria.…”
Section: Antivirulence Activities Of Indoles Against Non-indole-produmentioning
confidence: 96%
“…To date, over 85 bacterial species, both Gram negative and Gram positive, have been reported to produce indole, whereas both indole‐producing and non‐indole‐producing strains of bacteria will adapt their behavior in response to extracellular indole 8. 9, 10 It has been shown that indole controls a variety of key pathogenic phenotypes. In E. coli, indole decreases acid resistance,11 induces the expression of multidrug exporter genes and increases antibiotic resistance 12.…”
Section: Introductionmentioning
confidence: 99%